RESUlTS OF COMPARATIVE FISHING TRIALS WITH RECTANGULAR FlAT AND RECTANGULAR CURVED OTTER BOARDS - DESHPANDE,, S D; SIVAN, T M; RAMARAO, S V. S. (Fishery Technology, 2025)
Rectangular flat and rectangular curved otterboards were testedunder identical conditions and their relative efficiency ascertainedon the basis of catch landed by 137m four-seam shrimp otter trawl.During the study, significant increase was observed in the catch whenthe gear was rigged with curved otterboards. The horizontal spreadberween rectangular otterboards was found to be more by 13% ~ndthey also offered about 10% more towing resistance than the convent~ional boards. The otter boards were tested under trawling speed of2 knots per hour.